Polymeric optical fibre sensor coated by SiO2 nanoparticles for humidity sensing in the skin microenvironment - Gomez, David; Morgan, Stephen P.; Hayes-Gill, Barrie R.; Ricardo, Correia; Korposh, Sergiy (Elsevier, 2018)
The sensitivity of a low-cost polymeric optical fibre humidity sensor based on transmittance changes due to evanescent wave absorption is reported using test measurements in an environmental chamber and of the skin. The layer-by-layer method was used to coat 30mm of the central unclad section of a multimode polymeric optical fibre with 7 layers of a hydrophilic film consisting of bilayers of poly(allylamine hydrochloride) and SiO2 mesoporous nanoparticles. Sensor characterisation shows a decrease in light transmission as relative humidity increases as a result of refractive index changes of the coating deposited onto the optical fibre which correlates with a commercial capacitive humidity sensor. The sensitivity obtained for the sensor coated with an optimum 7 layers was approximately -3.87x10-3 and -9.61x10-3 in transmittance percentage per RH percentage for the range of ~10% to ~75% RH and 90% to 97% RH, respectively. In addition, a response time of 1.5s can be seen for breath monitoring with the polymeric optical fibre humidity sensor. The proof of concept measurements made on the skin indicate that this sensor has the potential to be used to monitor humidity of the skin microenvironment within a wound dressing which can be used to provide better prognosis of healing.